2007
DOI: 10.1002/ajmg.b.30503
|View full text |Cite
|
Sign up to set email alerts
|

Candidate gene association study of insulin signaling genes and Alzheimer's disease: Evidence for SOS2, PCK1, and PPARγ as susceptibility loci

Abstract: Epidemiological evidence supports the existence of a possible link between type II diabetes mellitus (T2DM) and late-onset Alzheimer's disease (LOAD). Polymorphisms from candidate genes for T2DM were genotyped in a two-stage approach to identify novel risk factors for LOAD. One hundred fifty-two polymorphisms were initially genotyped in a case:control cohort: nine SNPs showed individual association with disease status under at least one genetic model, while an additional two SNPs showed a haplotype association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 46 publications
(50 reference statements)
0
34
0
4
Order By: Relevance
“…20 As shown in the Table, overall, individuals who were homozygous for the GSK3B T-T haplotype do not show an association with disease risk (odds ratio, 1.22; p ϭ 0.098). However, in individuals with at least one MAPT H2 haplotype, the homozygous T-T haplotype was significantly associated with AD (odds ratio, 1.68; p ϭ 0.005).…”
Section: Association Of a Gsk3b Haplotype In Three Independent Alzheimentioning
confidence: 90%
See 1 more Smart Citation
“…20 As shown in the Table, overall, individuals who were homozygous for the GSK3B T-T haplotype do not show an association with disease risk (odds ratio, 1.22; p ϭ 0.098). However, in individuals with at least one MAPT H2 haplotype, the homozygous T-T haplotype was significantly associated with AD (odds ratio, 1.68; p ϭ 0.005).…”
Section: Association Of a Gsk3b Haplotype In Three Independent Alzheimentioning
confidence: 90%
“…20 Mean age of AD patients was 82 years (standard deviation [SD], 6.4). The samples were recruited from both community and hospital settings and an assessment battery was used to form a diagnosis of probable AD according to National Institute of Neurological and Communicative Diseases and StrokeAlzheimer's Disease and Related Disorders Association criteria.…”
Section: Subjects and Methods Subjectsmentioning
confidence: 99%
“…After full-text review, one study was excluded, because the study was a review. A total of eight studies met all the inclusion criteria and were considered in our meta-analysis, comprising 2948 patients with AD and 3753 controls (Sauder et al, 2005;Koivisto et al, 2006;Hamilton et al, 2007;Scacchi et al, 2007;Helisalmi et al, 2008;Yao et al, 2009;Combarros et al, 2011;Shibata et al, 2013). Eight studies (seven European, one Asian) with 3501 cases and 4622 controls considered the PPARg Pro12Ala polymorphism, and three studies (three European) with 553 cases and 869 controls considered the PPARg His447His polymorphism.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
“…The PPARg Pro12Ala and His447His polymorphisms have been studied in the context of AD (Sauder et al, 2005;Koivisto et al, 2006;Hamilton et al, 2007;Scacchi et al, 2007;Helisalmi et al, 2008;Yao et al, 2009;Combarros et al, 2011;Shibata et al, 2013). However, published results on the genetic associations of these PPARg polymorphisms are controversial and inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Glucose homeostasis is critical for energy generation, neuronal maintenance, neurogenesis, neurotransmitter regulation, cell survival and synaptic plasticity, thereby affecting cognitive function. 82,83 There is now an extensive body of evidence demonstrating the efficacy of PPARg agonists in ameliorating disease-related pathology and improved learning and memory in animal models of AD. 81 Recent clinical trials of the PPARg agonist rosiglitazone have shown significant improvement in memory and cognition in AD patients.…”
Section: Epiloguementioning
confidence: 99%